Pengaruh Keaktifan Berorganisasi, Prestasi Akademik, Lingkungan Belajar terhadap Kesiapan Kerja Universitas Tangerang - Kayla Anugerah Christianty Labiro; William Widjaja (Studi Ilmu Manajemen dan Organisasi, 2024)
Purpose: The importance of preparing students to enter the world of work is the main focus of a university. This research highlights XYZ University Tangerang and tries to analyze the factors that influence graduate work readiness. Researchers got 301 respondents from  2018 and 2019 Alumni. The purpose of this research is to analyze whether or not there is an influence between organizational activity, academic achievement, and learning environment on graduates work readiness at XYZ University Tangerang. Method: Researchers took 192 data who meet the requirements. Data collection used questionnaires and interviews method. The analysis technique used SmartPLS 3 application. Result: The results of this research shows that student activity and learning in organizations has a positive effect on work readiness of graduates of XYZ University Tangerang meanwhile academic achievement doesn’t have a significant effect on work readiness. Limitation: Researcher have limitations in accessing and contacting respondents. Contribution: It is hoped that the results of this research will provide valuable insight for universities in Tangerang to improving their quality of education in order to prepare students for work considering how tight the labor competition.